Teaching Sales Course in a Higher Learning Institution: Learning by Doing - Abdul Shukor, Syadiyah (International Business Education Journal, 2021)
It is an ultimate learning experience to be able to bridge theory and real-world practice in sales class.  Nonetheless, it is a challenge for educators in higher learning institutions to incorporate practical aspects into teaching.  In response, this study was conducted to expose students to perform selling in a real-life situation.  42 students enrolled in a professional selling course in a higher learning institution in Malaysia were given a selling task.  The students were asked to promote a financial product (i.e., insurance) to a potential client under the supervision of an insurance agent.  The task given to the students was part of the course assessment and carried out throughout a semester.  Students’ perceptions of the benefit gained from performing selling in the real sales environment were obtained through student evaluations at the end of the course.  This study indicated that the students had a positive selling experience, and the selling activities aided students’ understanding and interest in the course.